Organic and mineral fertilizer sources in Laelia anceps Lindl. subsp. anceps (Orchidaceae) in vegetative phase - Tejeda-Sartorius, Olga; Trejo-Téllez Libia Iris; Arguello-Quechuleño Mayra; Téllez-Vel María de los Ángeles Aída (Revista Mexicana de Ciencias Agrícolas, 2018)
The effect of organic and mineral fertilizers sources was evaluated, applied separately and in combination, on the growth of plants of Laelia anceps Lindl. sub sp. anceps (Orchidaceae) in vegetative phase (FV), classified in groups 1 and 2 (8 and 12 months of age, respectively), for evaluating their growth going from FV1 to FV2, and determine if it is possible to decrease the time between both phases. The experiment was conducted under greenhouse conditions; we used a substrate with 75% pine bark and 25% perlite. For group 1, the organic fertilization increased leaf length, number of roots, and root fresh weight and total. For group 2, the organic and mineral fertilization, separately, increased the number and length of leaves, organic fertilization increased leaf area, fresh weight of the pseudobulb and total. In group 2, organic and mineral fertilization, separately, increased the dry weight of the variables analyzed in relation to TEA, mainly. Ggroup 1 showed higher growth rates in the different variables, compared with group 2, but the dry weight in group 2 was between 5 and 7% higher compared to the dry weight of the group 1. Based on the findings, we conclude that organic and mineral fertilization applied separately, promote positive effects on growth variables analyzed in Laelia anceps subsp. anceps, and that this species requires eight months to go from FV1 to FV2.